Web-Based COT Monitoring Application for Operating Room Service Optimization - Muhammad Iqbal Aditya; Norma Yunita; Siti Marlina (SAN Scientific, 2026)
This study aims to develop a web-based COT Monitoring application that supports real-time operating room status monitoring at Universitas Indonesia Hospital. The problem addressed is the use of manual and spreadsheet-based monitoring, which caused information delays, input errors, and limited operational reporting. The study used a qualitative case study approach through observation, interview, documentation study, and literature review. The application was developed with the Waterfall model, covering requirements analysis, system design, coding, and Black Box Testing. The system provides login, real-time dashboard, user management, operation status management, operating room master data, and sequential status update features. Testing shows that the main functions met the expected outputs. The system currently runs on an internal hospital network and is not integrated with external hospital information systems. The article contributes a practical web-based monitoring design for improving information flow and transparency in operating room operations.